2019
DOI: 10.1101/19010280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain derived neurotrophic factor (BDNF) Val66Met polymorphism is not risk factor for bipolar disorder

Abstract: Bipolar disorder (BPD) is a psychiatric disease, characterized by the cycles of mania and depression. Several genetic studies investigated BDNF gene Val66Met polymorphism as risk factor for BPD, but results were inconclusive. Therefore, present meta-analysis was performed to reevaluate the BDNF Val66Met polymorphism and BPD association. Four databases (Pubmed, Springer Link, Science Direct and Google Scholar) were searched for eligible studies up to March 31,2018. Pooled odds ratios (OR) with 95% confidence in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The recent GWAS studies in European population could not confirm association of BDNF with BD (Cichon et al, 2011; Kohli et al, 2011; McMahon et al, 2010; Mühleisen et al, 2014; Sklar et al, 2011). While some meta-analyses on the European population have shown the Val allele to be associated with BD, there have been mixed results in other populations (González-Castro et al, 2015; Li et al, 2016; Rai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The recent GWAS studies in European population could not confirm association of BDNF with BD (Cichon et al, 2011; Kohli et al, 2011; McMahon et al, 2010; Mühleisen et al, 2014; Sklar et al, 2011). While some meta-analyses on the European population have shown the Val allele to be associated with BD, there have been mixed results in other populations (González-Castro et al, 2015; Li et al, 2016; Rai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Val allele was suggested to be associated in Caucasian populations (Frazier et al, 2014) whereas findings in Han Chinese population showed Met allele to be associated with BD (Wang et al, 2012; Xu et al, 2010). While some meta-analyses on the European population have shown the Val allele to be associated with BD, there have been mixed results in other populations (González-Castro et al, 2015; Li et al, 2016; Rai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%